Development and evaluation of a point‐of‐care test with a combination of EZ‐Fast DNA extraction and real‐time PCR and LAMP detection: evaluation using blood samples containing the bovine leukaemia DNA. (23rd September 2020) - Yamazaki, Y.; Thongchankaew‐Seo, U.; Nagao, K.; Mekata, H.; Yamazaki, W.
Abstract: Along with progress in globalization of society, the spread of infectious diseases has accelerated worldwide. The deployment of highly sensitive genetic tests is essential for early diagnosis and early containment of potential outbreaks and epidemics, as well as routine surveillance, although tedious and expensive nucleic acid extraction steps represent a major drawback. Here we developed a simple and rapid DNA extraction method, named as an EZ‐Fast kit, applicable to the field setting. The kit does not require advanced laboratory equipment or expensive DNA extraction kits and achieves crude DNA extraction within 10 min at extremely low cost and can easily be performed in field settings. When combined with real‐time PCR and LAMP analyses, the performance of the POCT, using 183 bovine blood samples, was similar to that of the existing DNA extraction method: 92·5% (135/146) (real‐time PCR) and 93·7% (133/142) (LAMP) diagnostic sensitivities, and 100% diagnostic specificities. The developed POCT provides a powerful tool to facilitate on‐site diagnosis in a field setting. Abstract : Significance and Impact of the Study : We developed and evaluated a point‐of‐care test (POCT) with a combination of new rapid DNA extraction method and real‐time PCR and LAMP detection suitable for field settings that does not require advanced laboratory equipment and expensive DNA extraction kits. The developed POCT achieves crude DNA extraction within 10 min at extremely low cost, and high diagnostic performance under combined use of real‐time PCR and LAMP analyses. This economical, easy, rapid, highly sensitive and specific POCT promises to provide an important new tool for routine veterinary medicine as well as zoonotic diseases in a field setting.